THE RELATIONSHIP BETWEEN SELF-ACCEPTANCE AND PEOPLE PLEASER IN LATE ADOLESCENTS WHO EXPERIENCED PARENTAL DIVORCE - Nur Agnes Devina; Sitti Murdiana (Adisam Publisher, 2024)
The aim of this research was to determine the relationship between self-acceptance and people pleaser in late adolescents who experienced their parents' divorce. Sampling was carried out using the snowball sampling technique, totaling 134 adolescents aged 17-22 years who had divorced parents. People pleaser was measured using the Disease to Pleaser Triangle scale from Braiker (2001) and self-acceptance was measured using the Self-Acceptance scale based on aspects of self-acceptance from Sheerer (1949). The results of hypothesis testing using Spearman rho correlation analysis show a correlation coefficient value of r = -0.574 and a significant value of p <0.01. This means that there is a negative relationship between self-acceptance and people pleaser in late adolescents who experienced their parents' divorce. Thus, the lower the self-acceptance, the higher the people pleaser of adolescents and vice versa. It is hoped that the results of this research will allow teenagers with divorced parents to increase self-acceptance as an effort to reduce the level of people pleaser.